2017
DOI: 10.1186/s13601-017-0169-4
|View full text |Cite
|
Sign up to set email alerts
|

Peak nasal inspiratory flow as outcome for provocation studies in allergen exposure chambers: a GA2LEN study

Abstract: BackgroundThe GA2LEN chamber has been developed as a novel mobile allergen exposure chamber (AEC) allowing standardized multicenter trials in allergy. Hitherto, subjective nasal symptom scores have been the most often used outcome parameter, but in standardized modern trials objective parameters are preferred. Despite its practicability, the objective parameter peak nasal inspiratory flow (PNIF) has been rarely used for allergy trials in the setting of allergen exposure chambers. This study aims to evaluate PN… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…Peak nasal inspiratory flow evaluation is the second most common technique of nasal patency assessment as part of NPT and is an alternative to RMM [26]. The PNIF is a very useful parameter in assessing the effectiveness of immunotherapy in pharmacological studies, as well as in assessing nasal patency in the context of surgical procedures [27].…”
Section: Peak Nasal Inspiratory Flow Testingmentioning
confidence: 99%
See 3 more Smart Citations
“…Peak nasal inspiratory flow evaluation is the second most common technique of nasal patency assessment as part of NPT and is an alternative to RMM [26]. The PNIF is a very useful parameter in assessing the effectiveness of immunotherapy in pharmacological studies, as well as in assessing nasal patency in the context of surgical procedures [27].…”
Section: Peak Nasal Inspiratory Flow Testingmentioning
confidence: 99%
“…Inability to accurately interpret assessment findings may yield a false positive test result. A 7-hour observational study of spontaneous changes in nasal patency measured by a PNIF meter and RMM showed variability of the respective evaluated parameters by 15.78% and 26.38% [26]. This is why it is so important to bilaterally assess changes in nasal patency (following an earlier allergen application into both nostrils) and, at the same time, use a subjective grading of the patient's discomfort.…”
Section: Acoustic Rhinometry In Allergen-specific Nasal Provocation Tmentioning
confidence: 99%
See 2 more Smart Citations
“…Many allergen exposure chambers exist and a EAACI Position paper attempted to harmonize current concepts and projecting the needs for the future [ 26 ]. Peak nasal inspiratory flow was found to be as outcome for provocation studies in allergen exposure chambers in a GA 2 LEN study [ 27 ].…”
Section: Diagnosismentioning
confidence: 99%